Counterproductive Effects of Rice For Poor (Raskin) Program on Labor Supply - Eka Riski Ningtiyas (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2018)
This study aims to examine the existence of the counterproductive effects of Rice For Poor (Raskin) program on labor supply. The impact evaluation is done by a combination of Difference-in-Difference and Propensity Score Matching methods. The estimation results have shown that Raskin has a significant impact on decreasing of households head working hours, especially on male. Based on these findings, it can be concluded that Raskin has a counterproductive effect on labor supply, but there is no evidence to say Raskin makes people lazy.